Rethinking Standardized Testing in English Language Proficiency: Moving Toward Culturally Responsive Assessment Models - Timothy Ojochegbe, Ameh (Jurnal Pendidikan Indonesia, 2024)
This paper explores the limitations of traditional standardized English language proficiency tests and advocates for the development and implementation of culturally responsive assessment models. While standardized tests such as TOEFL and IELTS are widely used to assess English proficiency, they often fail to account for the cultural and linguistic diversity of test-takers, leading to biases that disadvantage non-Western learners. This study examines existing research on cultural bias in language testing and proposes new assessment models that integrate cultural sensitivity and inclusivity. Using both qualitative and quantitative data, the paper outlines a framework for designing more equitable English language assessments, aimed at fostering fairness and improving the validity of language proficiency measures. The findings provide actionable recommendations for educators, policymakers, and test developers seeking to create assessments that reflect the diverse backgrounds and experiences of global learners